"We Are the Visible Proof": Legitimizing Abortion Regret Misinformation through Activists' Experiential Knowledge. (27th December 2017) - Doan, Alesha; Candal, Carolina Costa; Sylvester, Steven
Abstract : Since 2010, many abortion policies emerging at the state level have been designed around the idea of "abortion regret, " a scientifically discredited assertion that abortion causes long‐term health problems for women. Studies have examined the legal significance of regret claims in case law as well as the role scientific misinformation and uncertainty play in the policy process. However, scholars have given less attention to the intersection between abortion regret experiences and misinformation. We address this gap in the literature by examining how antiabortion activists' experiential knowledge continues to reinforce and legitimize misinformation contained in state policies. We explore the process of substantiating abortion regret misinformation by attaching it to activists' experiential expertise. Based on twenty‐three interviews with antiabortion activists, we argue that misinformation receives validation through the certainty of experiential knowledge, which activists mobilize around and use as a source of evidence in the policy process.